Managing knowledge in academic libraries.: Are we? Should we? - Daland, Hilde (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
This article gives an overview of the field of knowledge management and suggests how this can be applied to academic libraries. A literature review has been conducted and has been subject to a critical analysis of comparison to IFLAs standard for “Continuing Professional Development: Principles and Best Practices” (IFLA, 2015). Here IFLA has identified 10 points of best practice. These 10 points will be measured against the literature in the field of knowledge management to ascertain if academic libraries would benefit from a stronger relation to knowledge management.